Manuel Castells: A critical approach to the sociology of the city - Abdelhalim MAHOURBACHA (Social Sciences Journal, 1970)
This research paper aims to examine the critical approach formulated by Manuel Castells in the sociology of the city, and seeks to clarify the nature of the criticism that Castells directed at the ecological perspective of the Chicago School in studying the modern city, and his criticism of urban culture as a subject of research in urban sociology, and addressed the concept of urbanization as the social production of social formations. The paper also revealed the relationship between the urban issue and urban policies and showed the impact of political and economic factors on city planning. It explained how the city was transformed into a space for urban protest movements, and the research paper referred to the empirical studies and research that Castells completed, testing his hypotheses and research concepts